CATHODE REDUCTION OF ALIPHATIC ALDEHYDES ON CADMIUM ELECTRODE FOR REGENERATION OF USED MOTOR OILS - Ledovskykh, Volodymyr; Davydenko, Oleksandr; Rogova, Eugenia (Proceedings of National Aviation University (archive), 2014)
The results of studies of aliphatic aldehydes electroreduction as products of oxidation of motor oils oncadmium cathode in sulfuric acid-water-alcohol media are provided. With potentiostatic polarization measurementswas determined the diffusion mechanism of the cathodic process and conditions of its proceeding. Chromatographicanalysis has revealed the major products of aldehyde electroreduction – the corresponding alcohols andhydrocarbons.